Validating Motives of Autonomous Players (MAP) inventory: a bottom-up model of general motivational factors to videogame play - Vahlo, Jukka; Tuuri, Kai (Springer Science and Business Media LLC, 2025)
In this study, we develop and validate Motives of Autonomous Players (MAP) inventory. Several models on videogame motives have been published recently, but typically these models focus either on specific videogame types, on individual games, or on a particular theory on human motivation. The MAP model takes an integrative approach that considers why people play games in general. This is done by adopting an inductive bottom-up research attitude and by focusing on motives that can be argued to be broadly applicable for all kinds of videogames, ranging from casual mobile games to massively multiplayer online role-playing games. Since the MAP model is based on extensive player data that represent a great variety of player motives, the results are widely applicable in player modeling and in understanding player-game interaction at large. The initial MAP model was developed by analyzing open-ended gaming motive descriptions (N = 1,648) by a content analysis procedure. A preliminary 101-item MAP inventory was included in a UK-based survey (N = 600). A nine-factor model was identified and further validated as a 34-item version by making a confirmatory factor analysis with a USA-based survey data (N = 600). Additional analyses on construct validity were performed for investigating how motives to play videogames predict players' game enjoyment factors that were kept analytically distinct from general motivational factors to play videogames.